Desain Pembelajaran dengan Tujuan untuk Meningkatkan Kreativitas Siswa dengan Inovatif dan Aktif - Wahidatul Munandar; Muhiddin Palennari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Education is one of the rights owned by all Indonesian people, especially in the formation of intellectual skills of students, including in increasing creativity. The purpose of this writing is to provide analytical results related to learning design with aim of increasing student creativity with innovation and creativity. The writing method used in writing this journal is using qualitative type. The conclusion drawn through the explanation above is that increasing student creativity can be influenced by the use of learning designs designed by teachers. There are various designs used in the field of learning including ADDIE design, problem-based learning design, STEAM, and ILAB. The use of this learning design must of course be adjusted to the characteristics material and students. Learning design is a plan that is used as reference in implementation teaching and learning activities which include assessment, techniques, media, learning materials, and learning objectives.